2012
DOI: 10.1063/1.4745843
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth and metal-insulator transition of vanadium oxide thin films with controllable phases

Abstract: Articles you may be interested inOptimization of the semiconductor-metal transition in VO2 epitaxial thin films as a function of oxygen growth pressure Appl. Phys. Lett. 104, 081913 (2014); 10.1063/1.4866806 Improved metal-insulator-transition characteristics of ultrathin VO2 epitaxial films by optimized surface preparation of rutile TiO2 substrates Appl. Phys. Lett. Comprehensive study of the metal-insulator transition in pulsed laser deposited epitaxial VO2 thin films J. Appl. Phys. 113, 043707 (2013); 10.10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 19 publications
5
37
0
Order By: Relevance
“…The in-plane lattice parameter of the VO x film is clearly shorter than the bulk VO x , due to the presence of a compressive in-plane strain. 18 The above XAFS analysis further corroborates the occurrence of a M1 phase in the VO 2 film on theAl 2 O 3 1010 substrate. The increased intensities of the V-O and V-V shells for the VO 2 films reflect the higher degree of ordering if compared with a VO 2 powder sample.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The in-plane lattice parameter of the VO x film is clearly shorter than the bulk VO x , due to the presence of a compressive in-plane strain. 18 The above XAFS analysis further corroborates the occurrence of a M1 phase in the VO 2 film on theAl 2 O 3 1010 substrate. The increased intensities of the V-O and V-V shells for the VO 2 films reflect the higher degree of ordering if compared with a VO 2 powder sample.…”
Section: Resultssupporting
confidence: 62%
“…14,15 At present, a large number of studies focus on the preparation of high quality VO 2 thin films, since homogeneous films show reproducible SMT characteristics with no degradation. Until now, VO 2 films have been prepared with various techniques, such as the chemical vapor deposition (CVD), 4,16 the sol-gel method, 3,17 the polymer-assisted deposition (PAD), 18 the magnetron sputtering 19 pulsed laser deposition (PLD). 20,21 Among them, the sol-gel method has unique advantages such as a low cost, a simple preparation process, an uniform doping and it is suitability to prepare films with a large area, 22 a promising and mandatory condition for any VO 2 -based "smart window" applications.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on iron oxide [10] and vanadium oxide [11] have also been reported. Cobalt oxide has two stable oxide phases; CoO (rock-salt structure, a = 0.426 nm) and Co 3 O 4 (normal spinel structure, a = 0.808 nm).…”
Section: Introductionmentioning
confidence: 95%
“…The narrow hysteresis, ΔT = 3 K, obtained in this study is equivalent to single crystal or epitaxial films and is ideal for high performance applications2527. The self-assembled VO 2 disordered metamaterial films operate optimally even after extensive and extended use, which makes it an attractive candidate for highly demanding applications.…”
Section: Resultsmentioning
confidence: 78%
“…Polycrystalline and epitaxial films have been grown by various deposition techniques including Sol gel17, Pulsed Laser Deposition (PLD)4, Molecular Beam Epitaxy (MBE)18, Atomic Layer Deposition (ALD)19, Sputtering20, and Chemical Vapor Deposition (CVD)212223. Epitaxial films grow on pre-treated and appropriately oriented Al 2 O 3 or TiO 2 substrates or buffer layers242526. The SMT-relevant indicators of the VO 2 films quality are the amplitude of resistivity change and hysteresis width.…”
mentioning
confidence: 99%